Análisis de las causas y efectos del alcoholismo en los adolescentes del sector la esperanza, en la parroquia Venus del rio Quevedo, año 2014 - Medina Bailon, Lucia Maria (2015)
The study of the causes and effects of alcoholism in teens is a worrying social problem worldwide , where the numbers are soaring risk of accidents and diseases of death among young people , therefore, through this research was proposed as fundamental objectives, knowing the frequency and quantity of alcohol use in adolescents, the incidence of alcoholism in school performance of adolescents and analyze the association between alcohol consumption ratings and family relationships of young adolescents Sector Hope Venus parish Quevedo River . Surveys of 281 adolescents in 2014, reflected worrying figures, 67% of young people aged 13 to 15 years consume alcoholic beverages, accentuated alarmingly during weekends at friends or at bars and nightclubs. The analysis shows that intra-family problems, separation, divorce, physical and psychological abuse, abandonment of childcare to others , bad company and outings with friends on the weekend , were associated with having consumed alcohol in a 57 %, the main risk factors and excuses for not only the consumption of alcohol and snuff but a number of drugs and narcotics not allowed , which are sold in the same venues and now they are destroying the youth. The multi - causal nature of alcohol consumption in adolescence justifies preventive interventions are mainly directed to the modification of risk factors and protective of young adolescents. Added to this is the importance of parents in preventing this serious threat to their children, because they have to advise and encourage them to channel their energies through sport, study or work. Attention to this population to prevent hazardous drinking or intervene in situations where the problem exist, should be a priority in public health and not only the government but of the community in general.